2015
DOI: 10.1155/2015/315819
|View full text |Cite
|
Sign up to set email alerts
|

In VitroProperties of Potential Probiotic Indigenous Lactic Acid Bacteria Originating from Traditional Pickles

Abstract: The suitable properties of potential probiotic lactic acid bacteria (LAB) strains (preselected among 153 strains on the basis of their potential technological properties) isolated from traditional Çubuk pickles were examined in vitro. For this purpose, these strains (21 Lactobacillus plantarum, 11 Pediococcus ethanolidurans, and 7 Lactobacillus brevis) were tested for the ability to survive at pH 2.5, resistance to bile salts, viability in the presence of pepsin-pancreatin, ability to deconjugate bile salts, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
94
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 32 publications
15
94
1
4
Order By: Relevance
“…This is contrary to the resistance of the strains to high acidity, which confirms that there is no direct link between acid tolerance and tolerance to bile salts of lactobacilli [53]. Results of this study showing high survival of L. plantarum strains in the presence of bile salts are fully comparable to those of other authors [24,25,27,52,53]. The results showing adaptability to bile salts are also consistent with earlier findings [25,27].…”
Section: Resistance To Bile Saltssupporting
confidence: 91%
See 2 more Smart Citations
“…This is contrary to the resistance of the strains to high acidity, which confirms that there is no direct link between acid tolerance and tolerance to bile salts of lactobacilli [53]. Results of this study showing high survival of L. plantarum strains in the presence of bile salts are fully comparable to those of other authors [24,25,27,52,53]. The results showing adaptability to bile salts are also consistent with earlier findings [25,27].…”
Section: Resistance To Bile Saltssupporting
confidence: 91%
“…The highest level of survival in the presence of bile salts in MRS with glucose was observed for strains L. plantarum Lin2 and Pro, followed by Bom2, BB2, and 5.2. This is contrary to the resistance of the strains to high acidity, which confirms that there is no direct link between acid tolerance and tolerance to bile salts of lactobacilli [53]. Results of this study showing high survival of L. plantarum strains in the presence of bile salts are fully comparable to those of other authors [24,25,27,52,53].…”
Section: Resistance To Bile Saltssupporting
confidence: 82%
See 1 more Smart Citation
“…The highest hydrophobicity was shown by BMA 3.3 (55.492 ± 0.823). This value is lower than the results of the research of Tokath et al [28] who found hydrophobicity percentages from L. brevis MF105 of 97.96%, L. plantarum MF265 of 82.41%, L. brevis MF949 of 67.29%, and L. brevis MF493 of 62.36%. These four isolates were categorized as probiotics.…”
Section: Hydrophobicity Of Lactic Acid Bacteriacontrasting
confidence: 74%
“…The first line of contact is the mucus which acts as a protective layer due to its hydrophobic nature, thus the hydrophobicity of bacterial surface could play a significant role favouring the contact with host and promoting the second stage of adhesion by specific cell wall components (Haddaji et al, 2015). Hydrophobicity of cell envelope has been proposed as a simple screening index to test the ability of bacteria or yeasts to adhere to mucosa (Dhewa et al, 2009;Bautista-Gallego et al, 2013;Perricone et al, 2014a;Tokatli et al, 2015;Corbo et al, 2017;Speranza et al, 2017). Many authors reported that a microorganism could be labelled as hydrophobic and able to potentially adhere to gut mucosa if hydrophobicity is at least 30-40%, whereas an index of 10-15% suggested a hydrophilic behaviour and the inability to adhere.…”
Section: Resultsmentioning
confidence: 99%